ANALISIS KINETIKA PENDUGAAN UMUR SIMPAN BENIH CABAI MERAH - Elisa Julianti, Soewarno T.Soekarto , Purwiyatno Hariyadi dan Atjeng M.Syarief (Jurnal Teknologi Industri Pertanian, 2005)
ABSTRACTModification of the Asni’s mathematical model was adopted to predict the shelf life of red chilli seeds,  based on the first order of kinetics in the deterioration process of seed viability.  Application of the modified model to storage experiments of red chilli seeds at different moisture contents of 14.3 % and above, the shelf life of the seeds was only one month or less,  at moisture contents of  6.5 to 10.6 %  was 4 to 26 months, while at very low moisture  contents was more than 26 months. From this research it was found that the safe moisture content in room temperature storage of  red chilli seeds required moisture content in the region of secondary bound water (between 4.0 – 12 % wet basis). For very long shelf life  the seeds could be stored in the region of primary bound water ( bellow 4.0 % moisture), but along with the risk of  hard seed phenomenon. Key words : Seeds, Red Chilli, Shelf Life, Storage, Mathematical Model